The thermal degradation of poly(iso-butyl methacrylate) and poly(sec-butyl methacrylate) - IVANKA G. POPOVIC (Journal of the Serbian Chemical Society, 2000)
The non-oxidative thermal degradation of poly(iso-butyl methacrylate) and poly(sec-butyl methacrylate) was investigated by studying changes in the polymer residue. Due to the different number of b-hydrogens in their ester substituents, these two polymeric isomers behave differently when subjected to elevated temperatures. Poly(iso-butyl methacrylate) degrades quantitatively by depolymerisation with zip lengths of the same order of magnitude as those of poly(methyl methacrylate). Poly(sec-butyl methacrylate) degrades by a combined degradation mechanism of depolymerisation and de-esterification. De-esterification becomes a significant thermolysis route at temperatures higher than 240°C.